Prove the following absorption properties of Boolean algebras. Give a reason for each step.?

Prove the following absorption properties of Boolean algebras. Give a reason for each step.

x + (x * y) = x and x * (x + y) = x

1 Answer

Relevance
  • atsuo
    Lv 6
    1 month ago

    x + (x * y) = (x * 1) + (x * y) because x = x * 1

    (x * 1) + (x * y) = x * (1 + y) by distibution law

    x * (1 + y) = x * 1 because 1 + y = 1

    x * 1 = x

    x * (x + y) = (x + 0) * (x + y) because x = x + 0

    (x + 0) * (x + y) = x + (0 * y) by distribution law

    x + (0 * y) = x + 0 because 0 * y = 0

    x + 0 = x

    • Login to reply the answers
Still have questions? Get your answers by asking now.